The Challenges of Beyond Human Dignity: An Analysis of the Foundation of Dignity in Christian Theology - Baybado, Jr., Pablito A.; Redoña, Marites R. (Asian Horizons, 2025)
This article explores the Catholic Church’s theological understanding of human dignity, focusing on Dignitas Infinita (infinite dignity) addressing contemporary discourses calling for beyond human dignity and its culture-based application. Thus, the dominant anthropocentric view of dignity is increasingly being contested. The crisis of the equation of being human and dignity lies in its contextual application of human rights. The emphasis on the rights of animals and sensitivity to culture, for example, as an application of human rights has rendered human dignity malleable and open to interpretation, thereby shaking its very nature as both inalienable and inherent to all human beings. By analyzing contemporary discourses on human dignity in the light of the document Dignitas Infinita and other related documents of the Church, this study aims to recover the stability of human dignity as a foundational structure of personal and social existence.